2021
DOI: 10.5267/j.msl.2021.4.007
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate social responsibility reduce financial distress? Evidence from emerging economy

Abstract: This work investigates the relational behavior of corporate social responsibility (CSR) and its effect on firms' financial distress (FD). The population of the study consists of all the non-financial firms presently listed in the equity market of Pakistan. The yearly data set of 213 non-financial companies is selected from 2005 to 2017 with total observations of 2769. The analysis of the study based on OLS regression, fixed effect, and random effect models. The study also uses the GMM technique to guard agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 0 publications
5
6
1
Order By: Relevance
“…This significant inverse relationship supports Yang et al’ s (2019) argument that a firm's participation in CSR activities attracts investment and establishes positive stakeholder relationships, which saves the firm from FD. Further, our findings are consistent with Zheng et al (2019), Al‐Hadi et al (2016), Shahab et al (2018), Boubaker et al (2020), Do (2021) and Khan et al (2021).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This significant inverse relationship supports Yang et al’ s (2019) argument that a firm's participation in CSR activities attracts investment and establishes positive stakeholder relationships, which saves the firm from FD. Further, our findings are consistent with Zheng et al (2019), Al‐Hadi et al (2016), Shahab et al (2018), Boubaker et al (2020), Do (2021) and Khan et al (2021).…”
Section: Resultssupporting
confidence: 93%
“…This supports the argument that a firm's engagement in CSR activities builds a relationship with the stakeholders, builds goodwill and provides easy access to capital in the time of need thus saving the firms from financial distress. results support the findings of Khan et al (2021), who conducted their study on PSX-listed firms and found the same negative relationship between CSR and FD among sample firms. This significant inverse relationship supports Yang et al's (2019) argument that a firm's participation in CSR activities attracts investment and establishes Among the control variables, leverage and firm size have a significant negative relationship with the Z-score.…”
Section: Impact Of Corporate Social Responsibility On Financial Distresssupporting
confidence: 88%
See 2 more Smart Citations
“…There have been several different methods proposed in the literature for measuring CSR. In this study, we followed the research conducted by Ehsan (2019), Farooq and Noor (2021) and Khan et al (2021), and we used a multidimensional financial approach. …”
Section: Methodsmentioning
confidence: 99%